EVALUATION OF COASTAL COMMUNITY EMPOWERMENT POLICIES IN SELAYAR ISLANDS REGENCY - Azizah, Andi Azka; Yamin, Muh Nur; Akib, Haedar (Universitas Negeri Makassar, 2025)
ThisresearchaimstodeterminetheevaluationofcoastalcommunityempowermentpoliciesinSelayarIslands Regency, specifically in Parak Village, Bontomanai District. This research uses qualitative methods and produces descriptive data. Data collection uses interview, documentation and observation techniques. The results of the research show that in the evaluation of coastal community empowerment policies in Parak Village, Bontomanai District, Selayar Islands Regency through the distribution of converter machine assistance, as seen from the six (6) indicators, there are three (3) indicators that have been running well, namelyefficiency,adequacyandlevelingofmatters.Thiscanbeseenfromtheoverallaiddistributionprocess which is considered successful because it runs smoothly and is in accordance with the program objectives, namely saving operational costs for fishermen and the process of nominating potential aid recipients is in accordance with program requirements, and there are three (3) indicators that are not yet running. well, namelyeffectiveness,responsivenessandaccuracy.Thiscanbeseenfromthenumberoffishermenwhodo not use the assistance as they should, only 19 people (27.53%) ofthe totalinformants numbering 69 people who until now are still using the assistance provided by the government according to with the aim of the empowerment program